Effects of 'The Vicious Worm' educational software on Taenia solium knowledge among key pork supply chain workers in Zambia. - Victor Vaernewyck; Kabemba Evans Mwape; Chishimba Mubanga; Brecht Devleesschauwer; Sarah Gabriël; Chiara Trevisan (Public Library of Science (PLoS), 2020)
The neglected zoonotic cestode Taenia solium is endemic in many low- and middle-income countries, including Zambia. The parasite infects humans and pigs, inflicting high socioeconomic and disease burdens in endemic areas. Health education is regarded as an important component in T. solium control and previous studies indicate that 'The Vicious Worm' may be an effective T. solium health education tool for Tanzanian medical and agricultural professionals and Zambian primary school students. This study aimed to assess the effects of health education using 'The Vicious Worm' among Zambian pork supply chain workers, because the pork supply chain greatly influences food safety and security in Zambia. Half-day educational workshops using 'The Vicious Worm' and subsequent follow-up sessions were organized in the Lusaka and Katete districts of Zambia in March and April 2019. Questionnaires were administered before, after, and three weeks after the use of 'The Vicious Worm' to assess the program's impact on knowledge uptake and short-term retention. Focus group discussions were conducted to assess the program's user experience and the participants' beliefs, attitudes, and insights. In total, 47 pork supply chain workers participated: 25 from Lusaka and 22 from Katete. Overall, knowledge about T. solium was significantly higher (p<0.001) both immediately after, and three weeks after the use of 'The Vicious Worm' compared to baseline knowledge. Focus group discussions indicated incipient attitudinal and behavioral change, as well as a positive reception of the software; with participants describing the software as simple, educative, and useful to share knowledge. The study results indicate that workshops using 'The Vicious Worm' may be effective for short-term T. solium health education among key pork supply chain workers. Follow-up studies are required to assess long-term effects, transfer of knowledge and behavioral change. However, educational interventions with 'The Vicious Worm' could be considered for integrated T. solium control programs in sub-Saharan Africa, especially if the educational content is further simplified and clarified.